2010
DOI: 10.1128/jvi.01270-10
|View full text |Cite
|
Sign up to set email alerts
|

The 3′ Untranslated Region of the Andes Hantavirus Small mRNA Functionally Replaces the Poly(A) Tail and Stimulates Cap-Dependent Translation Initiation from the Viral mRNA

Abstract: In the process of translation of eukaryotic mRNAs, the 5 cap and the 3 poly(A) tail interact synergistically to stimulate protein synthesis. Unlike its cellular counterparts, the small mRNA (SmRNA) of Andes hantavirus (ANDV), a member of the Bunyaviridae, lacks a 3 poly(A) tail. Here we report that the 3 untranslated region (3UTR) of the ANDV SmRNA functionally replaces a poly(A) tail and synergistically stimulates cap-dependent translation initiation from the viral mRNA. Stimulation of translation by the 3UTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…Both S-and L-IGRs act as bona fide transcriptional termination signals that generate nonpolyadenylated viral mRNA species whose 3= ends have been mapped to multiple sites within the distal site of the IGR (21,24). As reported for bunyavirus (40,41), which also has nonpolyadenylated mRNAs, the 3= UTR of arenavirus mRNA may be able to play a role as a surrogate for a poly(A) tail that recruits cellular components that promote the interaction between the 5= cap and 3= end of the mRNA to facilitate repetitive use of a released ribosome for efficient translation. Differences in sequence and structure at the 3= UTR might have contributed to the efficiency of formation of translational complexes and influenced virus protein expression.…”
Section: Discussionmentioning
confidence: 97%
“…Both S-and L-IGRs act as bona fide transcriptional termination signals that generate nonpolyadenylated viral mRNA species whose 3= ends have been mapped to multiple sites within the distal site of the IGR (21,24). As reported for bunyavirus (40,41), which also has nonpolyadenylated mRNAs, the 3= UTR of arenavirus mRNA may be able to play a role as a surrogate for a poly(A) tail that recruits cellular components that promote the interaction between the 5= cap and 3= end of the mRNA to facilitate repetitive use of a released ribosome for efficient translation. Differences in sequence and structure at the 3= UTR might have contributed to the efficiency of formation of translational complexes and influenced virus protein expression.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, UTRs of the Bunyaviridae family are presumed to contain signals for encapsidation by the viral NP to form RNPs, signals for regulation of transcription and replication and signals for packaging the RNPs into virions (Kohl et al, 2006;Mir and Panganiban, 2010;Vera-Otarola et al, 2010). Moreover, it was reported that viral UTRs also participated in host cell regulation networks (Flick et al, 2002;Habjan et al, 2008;Sriskanda et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…5Ј IRES activity can be enhanced by interaction with specific elements in 3Ј UTRs, leading to template circularization similar to that of host mRNAs (20,21,51,55,63). Protein-dependent cyclization involving the 3Ј poly(A) tail and 5Ј IRES has been characterized for picornaviruses (11) and Tobacco etch potyvirus, a member of the poliovirus superfamily (41,48).…”
mentioning
confidence: 99%